Studies in historical geography, agrifood/forestry & geographic thought in New Zealand : a thesis submitted for the degree of Doctor of Letters of Massey University - Roche, Michael (Massey University, 2016)
The work presented for this thesis includes journal articles, book chapters, and one book produced over the span of 30 years and falls into three main domains; historical geography, contemporary agrifood/forestry research, and studies in the history of geographic thought. The historical geography work is further divided into research on forest history in New Zealand, on society and environment, largely in New Zealand in the last decade of the 19th century and early decades of the 20th century, and writing on the discharged soldier settlement scheme. The agrifood research spans from pipfruit to the meat industry. The associated forestry research ranges from afforestation policy, to privatization, corporate forestry, and forest governance. The history of geographic thought research considers the beginnings and distinguishing characteristics of geography in New Zealand. These bodies of work make a sizable and diverse contribution to the geographical literature and to interdisciplinary enquiries amongst geographers, environmental historians, and rural sociologists.
Content beyond chapter one not included for copyright reasons
Keywords: Historical geography; Geography; Agricultural industries; Forests and forestry; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Human geography, economic geography